Aplikasi Pengolahan Data Pasien Puskesmas Tulung Selapan Kabupaten Ogan Komering Ilir Menggunakan Microsoft Visual Basic 6.0: Aplikasi Pengolahan Data Pasien Puskesmas Tulung Selapan Kabupaten Ogan Komering Ilir Menggunakan Microsoft Visual Basic 6.0 - AKHMAD SAYUTI (Fakultas Teknik Universitas Ibnu Sina, 2024)
Community Health Center Patient Data Processing Application Using Microsoft Visual Basic 6.0 is software designed to simplify patient data management at Community Health Centers. This application was developed to increase efficiency and accuracy in processing patient data, as well as providing fast and easy access to patient information for health workers. This system includes modules for patient registration, medical records, doctor schedules, payments and reports. Application development using Microsoft Visual Basic 6.0 was chosen because of its ease of use and ability to develop Windows-based applications quickly. The system creation method includes system analysis in the form of a Flowchart, system design in the form of a Context Diagram, DFD, ERD. The results of the system are applied in the form of web design using the PHP programming language and database management using MySQL with the Apache web server. This research methodology uses descriptive. Data collection methods use observation methods, interview methods and documentation. The method used in developing this software is the Prototype model which includes the stages of data collection, design process, prototype creation and evaluation and then improvement. The results of developing this application are expected to reduce errors in data recording, increase operational efficiency, and provide easy access to information. Thus, it is hoped that this application can improve the quality of health services provided by Puskesmas to the community.